2014
DOI: 10.1002/adfm.201400590
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Heteroatom‐Doped Carbon Nanofiber Networks Derived from Bacterial Cellulose for Supercapacitors

Abstract: 5104 www.MaterialsViews.com wileyonlinelibrary.comof heteroatom-doped carbon nanomaterials. In the past decades, there has been certain success in developing effective approaches for synthesizing heteroatomdoped carbon nanomaterials. [ 10,12,[16][17][18][19][20][21] However, despite great progress has been made, the preparation of different heteroatom-doped carbon materials is rarely a general strategy; furthermore, the preparation of these existing heteroatomdoped carbon materials, specifi cally 3D network mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
293
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 562 publications
(299 citation statements)
references
References 38 publications
5
293
0
1
Order By: Relevance
“…It should be noted that the N-dopants in CNFs originated from NH 4 + of (NH 4 ) 6 Mo 7 O 24 during the pyrolysis process, which is similar to other BC-derived N-doped CNFs prepared by annealing BC with ammonium salt. 21 The crystalline phase compositions of the products obtained at different concentrations of (NH 4 ) 6 Mo 7 O 24 solution were first examined by X-ray diffraction (Supplementary Figure S2). A broad peak near 22°can be attributed to the (002) planes of graphitic carbon.…”
Section: Theoretical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the N-dopants in CNFs originated from NH 4 + of (NH 4 ) 6 Mo 7 O 24 during the pyrolysis process, which is similar to other BC-derived N-doped CNFs prepared by annealing BC with ammonium salt. 21 The crystalline phase compositions of the products obtained at different concentrations of (NH 4 ) 6 Mo 7 O 24 solution were first examined by X-ray diffraction (Supplementary Figure S2). A broad peak near 22°can be attributed to the (002) planes of graphitic carbon.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…20 Our recent studies demonstrated that BC was an excellent precursor for producing heteroatom-doped carbon nanofiber (CNF) aerogels for energy storage and conversion. [21][22][23] In this work, using BC as 3D nanostructured carbon source, we report a facile method for synthesizing a non-noble-metal HER electrocatalyst consisting of ultrafine Mo 2 C nanoparticles embedded within 3D N-doped carbon nanofiber networks (Mo 2 C@N-CNFs) via a solidstate reaction between (NH 4 ) 6 Mo 7 O 24 and BC. Owing to the low-cost biomass precursor and simple preparation process, our developed method is environmentally friendly, inexpensive and easy to scale up.…”
Section: Introductionmentioning
confidence: 99%
“…These heteroatoms come from the molecular 12 backbones of the HPMSs. The presence of heteroatoms in carbon structure has been demonstrated to be efficient in promoting the specific capacity [10,12,[33][34][35]. As shown in Table 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon-based electrodes with higher specific surface area, porosity and higher electrical conductivity are favorable for increasing the capacity and energy density of the electrodes. On the other hand, carbon materials with special designed architecture could enhance the penetration and transportation efficiency of electrolyte ions, and thus can endow the electrodes with better electrochemical performance at high current densities [8,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, carbonaceous materials such as activated carbon (AC), carbon nanotubes (CNTs) and graphene, largely fulfill the above mentioned conditions, and have therefore been intensely investigated for supercapacitor applications. For instance, AC electrodes used in commercial supercapacitors provide gravimetric capacitances of 200-500 F g −1 and 130-230 F g −1 in aqueous and organic electrolytes, respectively [3][4][5][6][7][8][9][10][11][12][13]. Using novel carbons such as graphene-based materials as electrodes has resulted in significant progress in improving the specific gravimetric capacitance of carbon electrodes.…”
Section: Introductionmentioning
confidence: 99%